Salvianolic acid B from Salvia miltiorrhiza bunge: A potential antitumor agent - Guo, Sha-Sha; Wang, Zhen-Guo (Frontiers in Pharmacology, 2022)
Salvia miltiorrhiza Bunge (Lamiaceae) is a perennial herb widely found in China since ancient times with a high economic and medicinal value. Salvianolic acid B (Sal-B) is an important natural product derived from Salvia miltiorrhiza and this review summarizes the anticancer activity of Sal-B. Sal-B inhibits tumor growth and metastasis by targeting multiple cell signaling pathways. This review aims to review experimental studies to describe the possible anticancer mechanisms of Sal-B and confirm its potential as a therapeutic drug.